2000
DOI: 10.1152/ajpregu.2000.279.5.r1659
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channels in primary cultures of seawater fish gill cells. II. Channel activation by hypotonic shock

Abstract: Previous studies performed on apical membranes of seawater fish gills in primary culture have demonstrated the existence of stretch-activated K(+) channels with a conductance of 122 pS. The present report examines the involvement of K(+) channels in ion transport mechanisms and cell swelling. In the whole cell patch-clamp configuration, K(+) currents were produced by exposing cells to a hypotonic solution or to 1 microM ionomycin. These K(+) currents were inhibited by the addition of quinidine and charybdotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…RVD occurs through an efflux of K ϩ , Cl Ϫ , and organic osmolytes accompanied by osmotically obligate water loss (20,28). We have previously demonstrated the presence of stretch-activated K ϩ channels in sea bass gill cells and discussed their mechanosensitivity during hypotonic-induced cell swelling (12,13). This study focuses taurine permeability in response to hypoosmotic shock.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…RVD occurs through an efflux of K ϩ , Cl Ϫ , and organic osmolytes accompanied by osmotically obligate water loss (20,28). We have previously demonstrated the presence of stretch-activated K ϩ channels in sea bass gill cells and discussed their mechanosensitivity during hypotonic-induced cell swelling (12,13). This study focuses taurine permeability in response to hypoosmotic shock.…”
Section: Discussionmentioning
confidence: 98%
“…When asymmetrical osmotic shocks were applied, we observed higher permeability and sensitivity of the basolateral membrane compared with the apical membrane. In a previous study, we described the relative impermeability of the apical side of sea bass gill epithelium in culture toward Cl Ϫ when measuring 125 I flux (reflecting chloride flux) during asymmetrical hypoosmotic shock (13). Moreover, Gilmour et al (15) found a reduction of the transcellular permeability and an increase in transepithelial resistance when the apical membrane of gill cells in culture was exposed to hypotonicity (freshwater).…”
Section: Taurine Permeability Of Basolateral Membrane Increases Durinmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, the presence of voltage‐sensitive K + efflux, inhibited e.g. by BaCl 2 , was reported in goldfish renal proximal tubules (Terreros et al, '90), sea bass ( Dicentrarchus labrax ) gill cells (Duranton et al, 2000b), trout red cells (Egée et al, 2000), Gobius niger enterocytes (Trischitta et al, 2004), turbot hepatocytes (Ollivier et al, 2006c), and Gilthead sea bream hepatocytes (Faggio et al, 2011). In contrast, BaCl 2 was without effect on swelling‐induced K + fluxes in rainbow trout hepatocytes (Bianchini et al, '88) and brown trout ( Salmo trutta ) proximal renal tubules (Kanli and Norderhus, '98), indicating not only cell‐specific, but also species‐specific differences in the expression of the transporter.…”
Section: Regulatory Volume Decrease In Fish Cellsmentioning
confidence: 88%
“…Although one study has suggested that CO activates K ATP channels (20), most (54 -56, 60) have focused more on CO binding and activation of large-conductance Ca 2ϩ -activated K ϩ (BK Ca ) channels. Previous studies have demonstrated the apparent presence of K Ca channels in isolated retinal ganglion cells from trout (26,27), and even charybdotoxin-sensitive gill epithelial cells from sea bass, Dicentrarchus labrax (16). However, these channels have yet to be characterized in trout vascular smooth muscle.…”
Section: Corm-3-induced Relaxation and Mechanisms Of Actionmentioning
confidence: 99%